Answer:
(x-4) (x-3) (x+3)
Step-by-step explanation:
x^3 - 4x^2 - 9x + 36
Make 2 groups
x^3 - 4x^2 - 9x + 36
We can factor out x^2 from the first group and -9 from the second group
x^2 (x-4) - 9(x-4)
Now factor out (x-4)
(x-4) (x^2 -9)
This may be an answer choice but we can still factor
(x^2 -9) is the difference of squares
(x^2-9) = (x-3) (x+3)
Replacing this
(x-4) (x-3) (x+3)
Answer:
A = 22 and B = 35
Step-by-step explanation:
The proportional value of x and y is simply
x times 3 1/2 = y
Answer:
60+1b
Step-by-step explanation:
Multiply the numbers without variables:
3x4=12
12x5=60
Next put the equations together:
60+1b
Hence, the correct answer is 60+1b